An Implausible Virtual Interview: Conversations with a Professional Research Subject - Owens, Lisa Lucile (Sociological methodology, 2022)
The author explores interactions with one research subject who feigns credentials and invents stories in order to participate in social science research interviews online. The possibility of intentional deception among interviewees in virtually mediated fieldwork is a critical consideration in the context of the recent extensive pivot to online-based fieldwork during the need for social distancing associated with the corona-virus disease 2019 pandemic. Following this rapid shift in what is generally accepted as the “gold standard” for social science research interviews, widespread use of online-based interviewing methods will likely endure as equivalent to in-person methods. A methodological case study with implications for virtually mediated fieldwork, this article highlights some of the advantages and disadvantages of virtually mediated interviews and provides practical suggestions.